Two new species and the molecular phylogeny of eight species of Macrostomum (Platyhelminthes: Macrostomorpha) from southern China - Lin, Yi-Tao; Feng, Wei-Tao; Xin, Fan; Zhang, Lv; Zhang, Yu; Wang, An-Tai (Zootaxa, 2017)
Two new species of Macrostomum (Platyhelminthes: Macrostomorpha), M. shiyanensis n. sp. and M. lankouensis n. sp. are described from Shiyan Reservoir and Lankou Town. Morphological characteristics of the penis stylets and sperm, as well as the phylogenetic analysis using concatenated sequences of 18S and 28S rDNA genes support the establishment of these two new species and indicate that they are closely related to M. sinensis and M. heyuanensis described from different regions of Guangdong province. Finally, the progress of molecular phylogenetics of Macrostomum worldwide is also discussed.